Objective and Subjective Determination of the Surface Visibility - Aydin Yagmur, Sensin; Serefhanoglu Sozen, Mujgan (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2019)
Surfaces in our environment are secondary light sources. They do not produce light, but reflector transmit the light that comes upon them.These surfaces which are transparent, translucent and opaque can be bright, silky or dull and coloured or colourless. The visibility of the surfaces can be assessed by two ways as objective and subjective. In the objective evaluation, luminance is affective which can be found by calculation and measurement and is the only photometric magnitude that can be seen. In the subjective evaluation, visibility changes as the logarithm of the visual stimulus depending on the physiological structure of the human eye. In other words, brightness that is the sensation of luminance (visual stimulus) is affective in subjective evaluation. The more luminance/brightness quantity, the more visibility of surfaces. But, it should be noted that high luminances create glare, low luminances provide ineffective surface visibility. In this study, visibility phenomenon and magnitudes that affect this phenomenon are explained, objective and subjective visibility of dull surfaces are examined.
Keywords: Visibility; visibility factor; luminance; brightness; Architecture